Improving Students' Critical Thinking during Covid-19 through Online Learning - Ambuy Sabur; Dadang Saepuloh; Reva Triana (Jurnal Pendidikan Edutama, 2021)
Abstract: The application of Problem Based Learning model by online learning during the Covid-19 period is one way to improve students' thinking abilities. This research aims to obtain empirical data about the comparison of student’s critical thinking skills levels by using the online based Problem Based Learning (PBL) model using the Zoom application and Whatsapp Grup in class X IPS SMAN 5 Tangerang Regency. The method of this research used quantitative that is quasi-experimental design. This research’s samples were class X IPS as an experimetal class or class A and class X IPS 2 as a control class or class B. The researcher analyzed the data in descriptive statistic by using SPSS 25 version. The results showed that applying the Problem Based Learning model has apositive impact on improving student’s critical thinking skills. Keywords: Problem Based Learning (PBL); Critical Thinking; Covid-19; Daring Abstrak: Penerapan model pembelajaran Problem Based Learning melalui daring pada masa covid-19 merupakan salah satu cara untuk meningkatkan kemampuan berpikir siswa. Tujuan penelitian ini untuk memperoleh data empiris tentang perbandingan tingkat berpikir kritis siswa dengan menggunakan model pembelajaran Problem Based Learning (PBL) berbasis onine dengan menggunakan aplikasi Zoom dan Whatsaap Grup pada siswa kelas X IPS SMAN 5 Kabupaten Tangerang. Metode penelitian ini menggunakan kuantitatif yaitu quasi eksperimen desain. Sampel dalam penelitian ini adalah kelas X IPS 1 sebagai kelas eksperimen atau kelas A dan kelas X IPS 2 sebagai kelas control atau kelas B. Pengumpulan  data dilakukan dengan tes, dokumentasi dan observasi. Peneliti menganalisis data secara statistic deskriptif dengan menggunkan SPSS 25 versi. Hasil penelitian menunjukan bahwa penerapan model Problem Based Learning berdampak positif dalam meningkatkan kemampuan berpikir kritis siswa. Kata kunci: Model Pembelajaran Berbasis Masalah; BerpikirKritis; Covid-19; Daring